Recognition of informal learning in Europe - criteria-based comparison of different approaches : paper presented at the Canada International Conference on Education (CICE-2012), University of Guelph, Ontario, Canada, June 18-21, 2012 - Annen, Silvia [Verfasser] (My University, 2012)
"In Europe the topic recognition of informal learning becomes more and more important. At the same time the Europe-wide as well as the national approaches dealing with recognition are rather diverse. To present the results of a systematic analysis of selected European approaches is the aim of this paper. Furthermore a synoptical comparison of these practical examples is presented. Due to the fact that the existing approaches have not been integrated in a consistent Europe-wide strategy for the recognition of competences, the systematic comparison of the approaches shall provide a basis for appropriate recommendations. In this paper selected European approaches for the recognition of informal learning are analysed, classified and evaluated with the help of the following theoretically derived criteria: objectives, methods, norms and standards, stakeholders, rights of disposal, coordination as well as signaling and screening." (Autorenreferat, BIBB-Doku)
Keywords: L 2.1.1 Informelles Lernen; S 2.2.4.4 Anerkennung non-formaler Qualifikationen; I 2.2 Europa; Informelles Lernen; Anerkennung; Verfahren; Europa